Fibroblast growth factor receptor (FGFR) inhibitor rogaratinib in patients with advanced pretreated squamous-cell non-small cell lung cancer over-expressing FGFR mRNA: The SAKK 19/18 phase II study. (October 2022) - Addeo, Alfredo; Rothschild, Sacha I.; Holer, Lisa; Schneider, Martina; Waibel, Christine; Haefliger, Simon; Mark, Michael; Fernandez, Eugenio; Mach, Nicolas; Mauti, Laetitia; Jermann, Philip M.; Alborelli, Ilaria; et al.
Highlights: Rogaratinib failed to improve PFS in patients with advanced squamous lung cell carcinomas overexpressing FGFR mRNA. Abstract: Background: Patients with advanced squamous-cell lung cancer (SQCLC) frequently (46%) exhibit tumor overexpression of fibroblast growth factor receptor (FGFR) messenger ribonucleic acid (mRNA). Rogaratinib is a novel oral pan-FGFR inhibitor with a good safety profile and anti-tumor activity in early clinical trials as a single agent in FGFR pathway-addicted tumors. SAKK 19/18 determined clinical activity of rogaratinib in patients with advanced SQCLC overexpressing FGFR1-3 mRNA. Methods: Patients with advanced SQCLC failing standard systemic treatment and with FGFR1-3 mRNA tumor overexpression as defined in the protocol received rogaratinib 600 mg BID until disease progression or intolerable toxicity. A 6-months progression-free survival rate (6mPFS) ≤15 % was considered uninteresting (H0), whereas a 6mPFS ≥38 % was considered promising (H1). According to a Simon 2-stage design, 2 out of 10 patients of the first stage were required to be progression-free at 6 months. Comprehensive Genomic Profiling was performedusing the Oncomine Comprehensive Assay Plus (Thermo Fisher Scientific). Results: Between July 2019 and November 2020, 49 patients were screened and 20 were classified FGFR-positive. Among a total of 15 patients, 6mPFS was reached in 1 patient (6.7 %), resulting in trial closure for futility after the first stage. There were 7 (46.7 %) patients with stable disease and 5 (33.3 %) patients with progressive disease. Median PFS was 1.6 (95 % CI 0.9–3.5) months and median overall survival (OS) 3.5 (95 % CI 1.0–5.9) months. Most frequent treatment-related adverse events (TRAEs) included hyperphosphatemia in 8 (53 %), diarrhea in 5 (33 %), stomatitis in 3 (20 %) and nail changes in 3 (20 %) patients. Grade ≥3 TRAEs occurred in 6 (40 %) patients. No associations between mutational profile and treatment outcome were observed. Conclusion: Despite preliminary signals of activity, rogaratinib failed to improve PFS in patients with advanced SQCLC overexpressing FGFR mRNA. FGFR inhibitors in SQCLC remain a challenging field, and more in-depth understanding of pathway crosstalks may lead to the development of drug combinations with FGFR inhibitors resulting in improved outcomes.